Stimulation of invariant natural killer T cells by α‐Galactosylceramide activates the JAK‐STAT pathway in endothelial cells and reduces angiogenesis in the 5T33 multiple myeloma model. (21st August 2014) - Nur, Haneen; Rao, Luigia; Frassanito, Maria Antonia; De Raeve, Hendrik; Ribatti, Domenico; Mfopou, Josué Kunjom; Van Valckenborgh, Els; De Bruyne, Elke; Vacca, Angelo; Vanderkerken, Karin; Menu, Eline
Summary Tumour pathogenesis in multiple myeloma (MM) correlates with a high vascular index. Therefore, targeting angiogenesis is an important therapeutic tool to reduce MM progression. This study aimed to investigate the role of invariant natural killer T (iNKT) cells in angiogenesis and the mechanisms behind the stimulation by α‐Galactosylceramide (α‐GalCer). We have previously found that α‐GalCer could increase the survival of 5T33MM mice and here we demonstrate that α‐GalCer reduces the microvessel density. We performed both in vivo and in vitro angiogenic assays to confirm this observation. We found that conditioned medium of α‐GalCer stimulated iNKT cells reduced neovascularization in the chick chorioallantoic membrane and in matrigel plug assays. Moreover, we observed a reduction in proliferation, migration and network formation and an induction of apoptosis upon exposure of murine endothelial cell lines to this conditioned medium. We furthermore observed that the JAK‐STAT signaling pathway was highly activated in endothelial cells in response to stimulated iNKT cells, indicating the possible role of IFN‐γ in the anti‐angiogenic process. In conclusion, these results highlight the possibility of recruiting iNKT cells to target MM and angiogenesis. This gives a rationale for combining immunotherapy with conventional anti‐tumour treatments in view of increasing their therapeutic potential.